Estudo e desenvolvimento de técnicas de controle para grafos de eventos temporizados - Guilherme Gomes da Silva (2012)
Systems governed by the occurrence of events and that have only phenomena of synchronization and time delay can be modeled by timed event graph. The dynamics of these systems can be described linearly through an algebra called max-plus algebra. With this algebra we can synthesize control strategies which make the systems respect the restrictions. In this paper we present two problems with different approaches. The first problem is to find the systems time of input based on just-in-time control. These times are found in two forms, the first usingmainly the theory of semimodules and the second using an alternate algorithm. The second problem discussed deals with the problem of finding a state feedback matrix, which ensures that the system does not violate the restrictions imposed on the state. Finally, in order to test the control obtained, these control methods were applied in manufacturing systems.